Tipología de cafetaleros/as e institucionalidad de sus organizaciones, elementos de participación en las políticas públicas en el sur del Ecuador. - Ramón Vivanco, Ángel Jamill (2014)
This research was conducted in the areas of coffee production region 7 of Ecuador, comprising the Loja, Zamora Chinchipe and El Oro provinces, linking grassroots organizations of the Federation of Small Organic Coffee Growers South - FAPECAFES, in its 6 grassroots: PROCAP, APECAM, APECAP, ACRIM, APEOSAE; and PROCAFEQ. Due to the importance of the production and marketing of coffee, among small and medium producers. The research focused on the analysis of social, productive, technological and economic variables to establish the typology of coffee producers, determining the degree of institutionalization of their organizations and participation and advocacy in public policy related to the coffee sector. The first hypothesis stated: "There implicative relationship between the type of coffee producer and the institutionalization of their organizations" so based on the analysis of socioeconomic and productive variables, a typology of producers was established and was related to the degree of institutionalization of organizations, concluding that the more productive and trained are the producers, the greater the degree of institutionalization of their organizations. The second hypothesis stated: "There implicative relationship between the institucionality of the coffee organizations and their degree of participation and the proposal for local and regional public policy"; so, once determined the degree of institucionality of the organizations, the degree of technical impact discussed in public policy, concluding that while institutional organizations still requires much work, the relationship is direct, so that the higher institucionality, greater their influence on public policy. The research included a plan to improve the product, institutional and political, which has been conducted participatory, and should be applied by FAPECAFES and their organizations. As set out recommendations to expand research in establishing territorial typologies, understanding the logic of the coffee production systems, upgrading of technical itineraries of cultivation, socio-organizational complexity; and analysis of the legal framework that promotes the participation of rural producers in public policy.